(untitled) (Fiep Bulletin - online, 2014)
Descriptive research that objectived identifying the sociodemographic and health characteristics of people with venous ulcers (VU) assisted on Onofre Lopes University Hospital (HUOL), in the city of Natal / RN. The target population is composed of 40 VU patients, attended by angiologists in surgical clinic ambulatory of this hospital. The study received assent of the Ethics Committee of Rio Grande do Norte Federal University (Protocol n.169/06). The data-collection was performed in surgical clinic ambulatory of HUOL, through structured interview, non-participant observation in the curative changes and VU patients’ records review. In this study, we had identified a clientele of VU patients predominantly female, mostly in an age group until 59 years, with low schooling and family income levels, unoccupied, featuring stories of venous insufficiency, of DVT, venous surgery and orthostatic position, with varicose veins, cardiopathy, HAS and diabetes. The characterization of this clientele could help in planning a full and resolutive assistance to people with VU and their families.